Cutaneous sarcoidosis and facial filling: a possible triggering event? - Iago Gonçalves Ferreira; Gustavo Bottene Ribolli; Luyze Homem de Jesus; Fabiane Cristina Lersch; Mariele Bevilaqua (Sociedade Brasileira de Dermatologia (SBD), 2022)
Sarcoidosis is a systemic granulomatous disease with skin involvement in 10% to 25% of cases.This skin condition has been associated with previous trauma, including the use of skin fillers.We present the case of a patient with an erythematous plaque on the nasal dorsum with 12 months of evolution and a history of previous facial fillings with polymethylmethacrylate and hyaluronic acid. Skin biopsy showed a granulomatous inflammatory process with an epithelioid pattern and multinucleated giant cells, characteristic of cutaneous sarcoidosis. Sarcoidosis can occasionally manifest without systemic involvement and may be associated with the previous use of long-term tissue fillers.